Macroscepis sinalobolana (Apocynaceae, Asclepiadoideae, Gonolobeae) a new and endemic species to Sinaloa, México - Alvarado-Cárdenas, Leonardo O.; Pío-León, Juan F.; Chávez-Hernández, María G. (Phytotaxa, 2022)
A new species of Macroscepis from Sinaloa, Mexico is described here. Macroscepis sinalobolana is morphologically similar to M. diademata and M. stevensii but differs in its corolla, gynostegial corona, and fruit morphology, as well as its distribution. Descriptions, illustrations, morphological comparisons, and geographic distribution maps of these species, together with its conservation status, are provided. This discovery is important because the diversity of the genus increases to five species in México, with three of them endemic to the country.